2018 Quinquennial Review of the Funds Capacity Development Strategy : Concept Note. (Policy Papers; Policy Paper, 2017)
(CD), including technical assistance (TA) and training, is one of the three core pillars of the Fund's work. Its main objective is to help member countries build institutions and capacity necessary to formulate and implement sound economic and financial policies. The Institute for Capacity Development (ICD) was established in 2012 with a specific mandate to further define and develop the Fund's strategy on capacity building and provide a clear institutional framework to bring the coordination and oversight over TA and training activities under one umbrella, while building on partnerships with donors. The Fund's capacity development strategy was last discussed by the Board in June 2013, and the Board subsequently endorsed the 2014 statement on IMF Policies and Practices on Capacity Development. The 2018 review of the CD strategy will include backward- and forward-looking components: The backward-looking component will consider the prioritization, funding, monitoring and evaluation, and delivery of CD as set out in the 2014 statement. The forward-looking component will provide the opportunity to outline reforms to increase the impact of CD. Emphasis will be on making CD more effective and efficient while building on its existing strengths. Conclusions from the 2018 review will be reflected in a revised statement on IMF Policies and Practices on Capacity Development.